Surfactant adsorption and Marangoni flow in liquid jets - Weiss, M; Weiss, Michael (2004)
This thesis is concerned with the interfacial behaviour of surfactant solutions on short time scales. A gravity-driven laminar liquid jet is used to create a rapidly expanding liquid surface, which exposes the surfactant solution to highly non-equilibrium surface conditions. This expansion causes the surface tension to differ locally from its equilibrium value, generating a (Marangoni) shear stress that acts on the jet surface and retards the surface acceleration. A boundary-layer treatment of the flow very near the nozzle shows that the cube-root dependence of the axial surface velocity on the distance travelled is altered through the adsorption of surfactant. A numerical model of the surfactant adsorption process in the jet has been developed within the framework of the computational fluid dynamics (CFD) program FIDAP. Complemented by the major results from the boundary-layer treatment the Marangoni stress at the detachment point does not exceed the shear stress inside the nozzle and the surface concentration at that point is finite a hybrid CFD model is presented. The hybrid CFD model is extended to incorporate the effects of micelle disintegration. This model extension assumes one micelle species, and the break-down of micelles is modelled using kinetic expressions. Results from the hybrid CFD model are computed for sub-micellar C16TAB and C14TAB, and for C16TAB in the presence of micelles. The computed results are validated with experimental data.